Role of vascular endothelial growth factor and placental growth factor expression on placenta structure in pre‐eclamptic pregnancy. Issue 10 (14th July 2015) - Kurtoglu, Emel; Altunkaynak, Berrin Z.; Aydin, Isinsu; Ozdemir, Ayse Z.; Altun, Gamze; Kokcu, Arif; Kaplan, Suleyman
Abstract Aim Pre‐eclampsia is a hypertensive disease that is characterized by high blood pressure and proteinuria after 20 gestational weeks and complicates 3–8% of all pregnancies. It is classified as either mild or severe pre‐eclampsia according to severity, and the aim of this study was to investigate the structural differences between these two classifications. Methods Placenta samples were collected from 68 women who underwent cesarean delivery. Total volume of villi and numerical density of vascular endothelial growth factor (VEGF)‐ and placental growth factor (PIGF)‐positive cells were estimated on stereology and evaluated using one‐way ANOVA. Results There was no significantly difference in total villi volumes between the groups (P > 0.05). In contrast, on immunohistochemistry, the numerical density of VEGF‐positive cells in severe pre‐eclampsia was significantly different to the control and mild pre‐eclampsia groups (P<0.05). Additionally, the numerical density of PIGF‐positive cells in the mild and severe pre‐eclampsia group was significantly higher than in the control group (P<0.01). Conclusion There is no relationship between villi volume and pre‐eclampsia, although growth factors play a role in placental changes. The present results were supported by histopathology and several studies in the literature.